PENGARUH FAKTOR MOTIVASI TERHADAP PRESTASI KERJA PEGAWAI BAGIAN KEUANGAN SEKRETARIAT DAERAH KOTA SAMARINDA - Anwar Arifin (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2021)
This research was conducted with the aim of knowing the work motivation of the employees of the Finance Section of the Regional Secretariat of Samarinda City. This research was conducted on 31 respondents from the population of employees who became the object of research by distributing questionnaires. The results of the analysis of this study concluded that; simultaneously independent variables consisting of: physiological needs (X1), security (X2), social needs (X3), appreciation (X4), and self-actualization (X5) proved to have a significant effect on employee motivation. Partially, the security variable is a variable that has a dominant influence on the work performance of the Finance Section of the Regional Secretariat of Samarinda City.